SURVEI POTENSI KEPURBAKALAAN GUA – GUA DI KECAMATAN WIWIRANO, KABUPATEN KONAWE UTARA MELALUI PENDEKATAN SISTEM INFORMASI GEOGRAFIS (SIG) - sandy suseno; Adha Mashur Sajiah; Ahmad Firman Tarta; Danial Danial; Wahab Wahab (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2019)
This study aims to determine the distribution of caves / niches that are potentially archaeological in the District of Wiwirano, North Konawe as well as identifying archaeological remains found at these sites. Next, the locational cave / niche aspect is examined with a Geographic Information System (GIS) approach. Through the GIS approach, the data summarized will be visualized in the form of a thematic map containing the distribution of caves / niches in the District of Wiwirano, North Konawe including archaeological information contained in these caves / niches.Data collection was carried out by direct observation in the Wiwirano District area, North Konawe. At the time of the observation, the astronomical coordinates of the cave / niche were recorded and also the archaeological remains at that location were recorded. The next step, classifying the collected data is followed by digitizing the data for mapping through the GIS approach. The expected results of this study are to become the main reference about the distribution of caves / niches in the District of Wiwirano, North Konawe. In addition, the results of this study can reveal the potential of archaeological remains in the region. This is in accordance with UHO's strategic objectives namely the provision of quality, relevant and competitive education services as well as the achievement of improved quality of research and service that has competitiveness, and community development rural-oriented. This research is also in line with UHO's strategic goal of producing a database that can be a reference for UHO archeology students in conducting their final project research.